Roadmap Guided Direct Percutaneous Vertebral Artery Puncture for Mechanical Thrombectomy of Acute Basilar Artery Occlusion: A Technical Case Report and Review of the Literature - Nawabi, Jawed; Bohner, Georg; Siebert, Eberhard (Frontiers in Neurology, 2022)
Access techniques for mechanical thrombectomy normally include percutaneous puncture of the common femoral or, more recently, the radial artery. Although target vessel catheterization may frequently not be devoid of difficulties via both routes, the vast majority of mechanical thrombectomy (MT) cases can be successfully managed. However, in a significant minority of cases, a stable target vessel access cannot be reached resulting in futile recanalization procedures and detrimental outcomes for the patients. As such, in analogy to direct carotid puncture for anterior circulation MT, direct vertebral artery (VA) puncture (DVP) is a direct cervical approach, which can constitute the only feasible access to the posterior circulation in highly selected cases. So far, due to the rarity of DVP, only anecdotal evidence from isolated case reports is available and this approach raises concerns with regard to safety issues, feasibility, and technical realization. We present a case in which bail-out access to the posterior circulation was successfully obtained through a roadmap-guided lateral direct puncture of the V2 segment of the cervical VA and give an overview of technical nuances of published DVP approaches for posterior circulation MT.